Book review: La nación pixelada. Costa Rica en Guanacaste: del multiculturalismo nacional a la transculturación latinoamericana, by Antonio Álvarez Pitaluga - Baltodano Zúñiga, Víctor Julio (2025)
This review provides a general assessment of the selected work. It does so by providing a panoramic analysis of its four chapters, based on their sections and contents, as well as the main theses and ideas supported and developed throughout its pages. It is assumed that the book proposes a new interpretation, from Latin America cultural history, of the role of Guanacaste in the national formation of Costa Rican culture and history, drawing on a non-traditional logic in contrast to the hegemonic narrative of national creation. Thus, it is accepted that the book can generate interesting debates among historians and other specialists. It also disagrees with certain reflections the author presents in the work. Finally, it concludes with a final interpretative assessment.